Reporter at Large - M V Kamath; KAMATH (M V) (Mumbai Bharatiya Vidya Bhavan, 2002)
This Book By The Noted Journalist M.V. Kamath Is A Reflective Analysis Of The History Of Modern India And Offers Insights Into The World Of Diplomacy, Politics And Journalists. Divided Into 5 Parts Followed By 3 Appendices. Also Has A Number Of Black And White Photographers.
Keywords: Journalism; Kashmir Debate; God's Own Country